2018
DOI: 10.1128/jvi.02063-17
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Reassortment Is Limited by Anatomical Compartmentalization following Coinfection via Distinct Routes

Abstract: Exchange of gene segments through reassortment is a major feature of influenza A virus evolution and frequently contributes to the emergence of novel epidemic, pandemic and zoonotic strains. It has long been evident that viral diversification through reassortment is constrained by genetic incompatibility between divergent parental viruses. In contrast, the role of virus-extrinsic factors in determining the likelihood of reassortment has remained unclear. To evaluate the impact of such factors in the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 57 publications
1
63
0
Order By: Relevance
“…The site of generation of airborne IAVs is the URT. In order to understand from which anatomical site of the respiratory tract airborne transmissible IAVs are expelled, untagged and genetically tagged variant (var) versions of the A/Netherlands/ 602/2009 virus (A/H1N1 and A/H1N1 var ) 30 were used to inoculate donor animals in the ferret transmission model 18,32 . The A/H1N1 var virus carries a single synonymous substitution per gene segment, so that it can be differentiated from the A/ H1N1 virus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The site of generation of airborne IAVs is the URT. In order to understand from which anatomical site of the respiratory tract airborne transmissible IAVs are expelled, untagged and genetically tagged variant (var) versions of the A/Netherlands/ 602/2009 virus (A/H1N1 and A/H1N1 var ) 30 were used to inoculate donor animals in the ferret transmission model 18,32 . The A/H1N1 var virus carries a single synonymous substitution per gene segment, so that it can be differentiated from the A/ H1N1 virus.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that double inoculations at different anatomical sites of the respiratory tract of ferrets led to compartmentalization of the viruses, which greatly restricted reassortment 30 . Therefore, next-generation sequencing was performed on only one gene, the PB2 gene, to determine whether the throat and nose swabs collected from the donor and recipient ferrets contained the A/H1N1, A/H1N1 var viruses or a mix of both viruses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reassortment data was used to calculate viral genotypic diversity; that is, the diversity of the 256 possible WT/VAR genotypes present in a given sample. Diversity was quantified as reported previously 80 , by calculating Simpson’s Index, given by D = sum( p i 2 ), where p i represents the proportional abundance of each genotype 81 . Simpson’s Index accounts for both the raw number of species and variation in abundance of each, and is sensitive to the abundance of dominant species.…”
Section: Methodsmentioning
confidence: 99%